Cocoa Producers’ Decision on Fermenting Beans in Jembrana Regency, Bali Province, Indonesia - Ambarawati, I Gusti Agung Ayu; Esterina, Ni Puspa Ayu (Advances in Social Sciences Research Journal, 2024)
Cocoa bean has an important role in the agricultural economy of Indonesia for its foreign earnings. Demand for high quality of cocoa beans is increasing fast due to the expansion of global cocoa and chocolate market. Bali Province also plays an important role in Indonesia’s cocoa production and export where the main cocoa plantation lies in Jembrana Regency cultivated by small-scale farmers. Chocolate industry requests for high quality cocoa beans from fermented cocoa for high prices, however farmers are still reluctant to do fermentation. This study aims at analyzing probability of farmer’s decision to ferment cocoa beans at Jembrana Regency, Bali Province, Indonesia. Logit regression was utilized where the dependent variable is in binary, which is the change in probability of a cocoa producer choosing to ferment their cocoa beans, given the independent variables included farm size, production and other occupation of farmers. The result from the average marginal effect shows that only production variable is significant to increase the probability of the cocoa farmers to ferment their cocoa beans. Result from the analysis indicates that on average for one kilogram increase in cocoa production per month, the probability of observing increases fermentation by approximately 0.26 percentage point. In other words, higher production volume increases the probability of the cocoa producers to ferment their cocoa beans. It is suggested to multi stakehonders in cocoa industry to further improve production through the implementation of good agricultural practices (GAP) and extending training for cocoa farmers.